Mae Dailey and others - Unknown:::Creator::::::::::::
Photograph shows a woman kneeling in front of Mae Dailey at the celebration of the 75th anniversary of the YWCA in San Jose. There are three other women sitting beside Mae and they are all along a wall with poster boards filled with pictures and information about the YWCA's services. The titles on the poster boards read: "Informal Education, Child Assault Prevention, [Chi]ld [Ca]re, Career Services, Parent Education."